SKRINING KEMAMPUAN PATOGENISITAS ISOLAT ACTINOMYCETES ASAL RHIZOSFER KOPI DALAM MENGINFEKSI TELUR DAN LARVA STADIUM 2 NEMATODA PURU AKAR Meloidogyne Sp. - Agustinur Agustinur; Siwi Indarti; Donny Widianto (Jurnal Agrotek Lestari, 2018)
Root-knot Nematode (Meloidogyne sp.) is one of plant-parasitic nematode causing a serious damage of coffee. The spread of this parasites occurs through the distribution the number of eggs on the plantation, while the process of infection in plants is acted by juvenile 2. Therefore, to solve this problem, several effort to decrease the infesting nematodes are needed. This may be done by using natural enemy that can suppress and control eggs and juvenile 2. The objective of this research was to determine the potency of pathogenicity of actinomycetes toward Meloidogyne eggs and juvenile 2. A total of 39 actinomycetes isolates were obtained from rhizosphere soil of coffee plantation from PT Perkebunan Nusantara XII, Bondowoso, East Java. The result of in vitro pathogencity screening showed that there are 5 isolates (P2A01, K1B1, P4A04, H106 and H203) than had the potency in controlling eggs and juvenile 2. Then, crude extract of the isolates tested on mature and immature eggs. The result showed that isolates H106 and P2A01 were able to control Meloidogyne by triggering immature egg hatching and increase juvenile mortality. While isolates P4A04, K1B1 and H203 could decrease the percentage of egg hatching as well as increase juvenile mortality. Keywords: Actinomycetes, Meloidogyne sp., Pathogenicity, Egg, Juvenile 2